Development of Motion Graphic as Education Material for Promoting Shipping Industry Using EPIC Model Testing - Mirza Oktanizar; Dwi Ely Kurniawan (IJNMT (International Journal of New Media Technology), 2021)
Education related to problems in the shipping industry to the general public who have no background in the shipping industry and activities when ships dock at the port becomes a challenge to conduct research. This research develops multimedia motion graphics to combine graphic design, animation, text, and sound in visualizing materials and activities in the shipping industry. Stages of making multimedia start from ideas, narration, storyboard, tracing, editing, rendering, and testing. The research uses the EPIC Model testing by paying attention to aspects of empathy, persuasion, impact, and communication. The results of testing the effectiveness of the EPIC model obtained an EPIC rate of 4.15, which means that the resulting motion graph falls within the effective range criteria. Index terms— multimedia; motion graphic; EPIC model; effectiveness